Preparation and performance of conductive tack coat on asphalt pavement. (10th August 2020) - Wang, Chaohui; Fan, Zhentong; Shu, Cheng; Han, Xiaoxia
Highlights: MEAWER and MWER tack coats are optimized and prepared by using carbon fiber as adhesive layer. The temperature change and bonding performance of two kinds of conductive adhesive layers are compared and analyzed. The best distribution of carbon fiber for two types of conductive adhesive layers is recommended. Abstract: The purpose is to solve the problems of inadequate snow melting uniformity, difficult construction, and large heat storage in existing energy conversion pavements for deicing and snow melting. The conductive layers of different adhesive materials were prepared with emulsified asphalt modified by waterborne epoxy resin (MEAWER) and modified waterborne epoxy resin (MWER) as matrix. According to the surface resistivity and temperature change, the conductivities and heat conduction effects of the two types of conductive adhesive layers were compared and evaluated, respectively, and the road performance is determined based on multiple conditions. The results showed that when the amount of carbon fiber was 120 g/m 2, compared to MEAWER, the surface resistivity of MWER was 18.7% lower, the surface temperature was 3.6 ℃ higher, and the bonding strength was 46.1% higher. The thermogenesis and heat dissipation efficiency of MWER could reach 6.9 and 2.76 ℃/h at −5 ℃, respectively. Moreover, its minimum shear and drawing strengths exceeded 1.3 and 0.5 MPa, respectively. Based on the temperature change and road performance of the conductive adhesive layer, it was recommended that 120 and 100 g/m 2 of carbon fiber be distributed in the MEAWER and MWER conductive tack coats, respectively.